2012
DOI: 10.1371/journal.pmed.1001245
|View full text |Cite
|
Sign up to set email alerts
|

HIV Treatment as Prevention: Systematic Comparison of Mathematical Models of the Potential Impact of Antiretroviral Therapy on HIV Incidence in South Africa

Abstract: Background Many mathematical models have investigated the impact of expanding access to antiretroviral therapy (ART) on new HIV infections. Comparing results and conclusions across models is challenging because models have addressed slightly different questions and have reported different outcome metrics. This study compares the predictions of several mathematical models simulating the same ART intervention programmes to determine the extent to which models agree about the epidemiological impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
312
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(325 citation statements)
references
References 72 publications
12
312
1
Order By: Relevance
“…Mathematical models have sought to predict the long‐term population‐level impact of UTT strategies on the epidemic 15, 16. All models have indicated that UTT could reduce HIV‐transmission, but the estimated impact of the UTT strategy on the reduction of HIV incidence ranged from 35% to 54% in the short‐term and from 32% to 74% in the longer term 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models have sought to predict the long‐term population‐level impact of UTT strategies on the epidemic 15, 16. All models have indicated that UTT could reduce HIV‐transmission, but the estimated impact of the UTT strategy on the reduction of HIV incidence ranged from 35% to 54% in the short‐term and from 32% to 74% in the longer term 16.…”
Section: Introductionmentioning
confidence: 99%
“…All models have indicated that UTT could reduce HIV‐transmission, but the estimated impact of the UTT strategy on the reduction of HIV incidence ranged from 35% to 54% in the short‐term and from 32% to 74% in the longer term 16. Furthermore, these models vary greatly in structure and in parametric assumptions and rely on context‐specific variables, such as eligibility criteria for ART initiation, uptake and coverage of HIV testing, linkage to care, treatment initiation and adherence 13.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling has played a key role in the discussion of the impact of treatment as prevention strategies, highlighted by the paper by Granich et al (2), and followed up by others (11)(12)(13)(14). These models all set out to assess the impact of treatment on population prevalence and incidence using simulations with parameter values estimated from various data sources.…”
mentioning
confidence: 99%
“…Modelling studies have explored the widespread use of ART but mainly in sub-Saharan settings [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], in the United States [90;91], in China [92][93][94], Canada [95] and for some specific groups, such as MSM in Australia [36;96;97], in Peru, Ukraine, Kenya and Thailand [98] and in different cities in the United States [99][100][101][102][103]; only a few of them model the HIV epidemic in European countries (MSM in Amsterdam, the Netherlands [104] and in the UK [105][106][107] and people who inject drugs in Russia [108]). They varied in their conclusions, although most have suggested potential appreciable beneficial effects on HIV incidence of introducing ART initiation at a higher CD4 count as a policy at a population level.…”
Section: European Population-level Impactmentioning
confidence: 99%